Effectiveness of Planned Teaching Programme on Knowledge Regarding the Secondary Growth and Developmental Changes in Early Adolescent Period (10-14yrs) - Raveena; Sarika Yadav; Khushbu (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background : The stage of adolescences is passing through the different level and period of growth, so it is very important and outstanding because the changes that occur during adolescence affect the family as well as the society1. The pubertal or physiological changes during this period include the adolescent’s growth spurt, gonadal growth, growth of secondary sexual organs and characteristics, changes in body composition and growth of respiratory, circulatory and muscular systems2. Objectives: The objectives of the study have drawn to fulfill the research reflecting on the effectiveness of planned teaching programme regarding secondary growth and developmental changes in early adolescent period (10-14yrs) among students studying in the selected Govt. school of Haryana. Material and method : The study was conducted at Govt. Sr. Sec. School, Nuna Majra ( Jhajjar) Haryana.100 students was selected for the study by using nonProbability convenient Sampling Technique. Knowledge of the children was assessed through the structured questionnaire and after that planned teaching programme was delivered to samples and after 7 days post test was conducted to the gained knowledge of children regarding secondary growth and developmental changes in early adolescent period. Result : The mean of pre-test skill score 9.88 and post-test skill score 24.63 having a significant difference with t- value for skill 30.90 at level of significant p<0.05. Post-test mean knowledge score was more than pre-test knowledge score with mean difference of 14.75. Paired t- test was performed to find the difference between pre-test and post-test knowledge score. Therefore, it was concluded that there was a significant difference in pre-test and post-test knowledge score to assess the effectiveness of planned teaching programme in terms of gain in knowledge score among children in early adolescent period (10-14yrs).